Multi-objective Optimization Strategy of User-Side Energy Storage Operation Differentiating Working / Nonworking Load - Weiwei SUN; Xiaowen KOU; Guang ZHOU; Manli LI (Zhongguo dianli)
Under the two-part electricity price, in order to make more efficient use of energy storage and improve the comprehensive benefits obtained by users, a user side energy storage multi-objective optimization strategy distinguishing working / nonworking load is proposed by constructing demand management, energy storage income, load fluctuation increase rate and SOC process control model. It can effectively realize the multi-objective optimization of reducing the monthly power consumption cost of users, reducing the increase rate of load fluctuation range and reducing the times of energy storage charge and discharge and standby state conversion. An example of a large industrial user is optimized by calling CPLEX solver with MATLAB to verify the feasibility of the strategy.